Machinablity of Al/ 10%SiC/ 2.5%TiB2 Metal Matrix Composite with Powder-mixed Electrical Discharge Machning. (2016) - Roy, Chethan; Syed, Khalid Hussain; Kuppan, P.
Abstract: In the present work, a study has been made to optimize the process parameters of powder mixed electrical discharge machining (PMEDM). Response surface methodology has been used to plan and analyze the experiments. Analysis were done to investigate the effects of the process parameters viz. pulse current (I), pulse on-time (Ton) and concentration of the Al powder in kerosene dielectric (C) and its effects on material removal rate (MRR), tool wear rate (TWR) and surface roughness (Ra). Process parameters were optimized for high MRR, low TWR and low Ra using desirability function approach of MINITAB software. Due to frequent short circuiting, addition of Al powder to the dielectric fluid reduces the MRR whereas TWR decreases for low peak current of 2 A with the increase in the concentration of powder. Addition of Al powder further improves the surface roughness to a value of 3.31 μm.